USING EXERCISES (PHYSICAL, SKILL) TO DEVELOPAGILITY AND THE SKILL OF DEFENDING THE FIELDWITH VOLLEYBALL - Ali Khalid Mukhlif (Proximus Journal Publishing, 2025)
Ali, O., & Hamid, H. (2021). Building of Psychological Directions Parameter for Anbar EducationalDirectorate Teachers for non-specialty Towards Practicing Classroom and Extracurricular Activities.Anbar University Journal of Physical Sciences and Sports, 12(23), 23–46.https://doi.org/10.37655/uaspesj.2021.175083Ali, O., Mushref, A., & Ali, B. (2024). The Role of Supplements in Improving Muscular Strength andEndurance in Professional Soccer Players: A Systematic Review. American Journal of Social andHumanitarian Research, 5(12), 485–497. https://doi.org/https://doi.org/10.31150/ajshr.v5i12.3116Juma Muhammad Awad, Ali Khaled Khalif, Volleyball, Basic Skills and Official Rules, 1st Edition,Central Press, Diyala University, 2022.Khalaf, H. H., Abrahim, A. A., Khaleel, N. M., Hummadi, J. N., Mushref, A. J., & Ali, O. A. (2024).THE IMPACT OF THE DINES MODEL AS AN EDUCATIONAL MEDIATOR ON COGNITIVEACHIEVEMENT AND LEARNING OVERHEAD PASSING SKILL IN VOLLEYBALL. ProximusJournal of Sports Science and Physical Education, 1(12), 70–71.Khalaf, Y. A., AbdulJabbar, M. A., & Ali, O. A. (2025). The effect of sports job burnout on theperformance of workers in student activities departments in Iraqi universities | El efecto del agotamientolaboral deportivo en el rendimiento de los trabajadores de los departamentos de actividades estudiantilesde. Retos, 66, 86–95. https://doi.org/10.47197/retos.v66.113271Khalil Ibrahim Al-Hadithi and Juma Muhammad Awad, Building and Codifying Skill Tests for DeepDefence of the Field with Volleyball, Anbar University Publication Research - College of PhysicalEducation and Sports Sciences, 2011.Mohamed Sobhi Hassanein and Hamdi Abdel Moneim: Scientific Foundations of Volleyball andMeasurement Methods for Evaluation, Book Center for Publishing, 1st Edition, 1997.Mohammed Hammood, Y., Hussein Rashid, A., & Adham Ali, O. (2025). The effect of a proposedtraining method using play exercises to develop specific agility and skill performance in football | Elefecto de un método de entrenamiento propuesto que utiliza ejercicios de juego para desarrollar laagilidad específica y el re. Retos, 63, 719–728. https://doi.org/10.47197/retos.v63.111095Mowaffaq Asaad Mahmoud Al-Hiti, Basics of Sports Training, 1st Edition, Syria, Dar Al-Arrab andDar Noor for Studies, Publishing and Translation, 2011.Najla Abbas Nassif and others: Basic Principles of Volleyball Skill and Methods of Learning, 1stEdition, Baghdad, Dar Al-Kutub and Archives, Baghdad, 2012
Keywords: physical; skill; volleyball